Pembuatan E-Brochure Sebagai Media Iklan Menggunakan Aplikasi Adobe Illustrator Pada PT Lingkaran Cendekia Jaya Kediri - Mochammad Sihabudin; Joni Dwi Pribadi; Umi Khabibah (CV. ITTC INDONESIA, 2025)
marketing activities. Technology greatly assists companies in creating effective digital ads that can influence consumer purchasing behavior. This study aimed to create effective e-brochure advertising media using the Adobe Illustrator application. The research method employed in this study is action research with observation and questionnaires. The measurement of design effectiveness uses the EPIC Models method. The result of the analysisshowed that the e-brochure design was categorized as a good and feasible design, with an average EPIC Rate score of 4.38. Based on the research result, it can be conclude that the e-brochure design is very effective for use as an advertising medium at PT Lingkaran Cendekia Jaya Kediri.